2016
DOI: 10.1055/s-0036-1597618
|View full text |Cite
|
Sign up to set email alerts
|

A Canine Arthroscopic Anterior Cruciate Ligament Reconstruction Model for Study of Synthetic Augmentation of Tendon Allografts

Abstract: Novel graft types, fixation methods, and means for augmenting anterior cruciate ligament (ACL) reconstructions require preclinical validation prior to safe and effective clinical application. The objective of this study was to describe and validate a translational canine model for all-inside arthroscopic complete ACL reconstruction using a quadriceps tendon allograft with internal brace (QTIB). With institutional approval, adult research hounds underwent complete transection of the native ACL followed by all-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Suspensory fixation may offer other biological advantages over interference screw fixation. Several authors have reported that interference screws provide a limited tendon-bone contact area because much of the tunnel circumference is occupied by the screw itself, while adjustable loop systems provide a greater contact zone [15,29], and allow "four-zone direct graft healing" which has been associated in animal study with the absence of tunnel widening on radiographic and histologic assessments [29].…”
Section: Discussionmentioning
confidence: 99%
“…Suspensory fixation may offer other biological advantages over interference screw fixation. Several authors have reported that interference screws provide a limited tendon-bone contact area because much of the tunnel circumference is occupied by the screw itself, while adjustable loop systems provide a greater contact zone [15,29], and allow "four-zone direct graft healing" which has been associated in animal study with the absence of tunnel widening on radiographic and histologic assessments [29].…”
Section: Discussionmentioning
confidence: 99%
“…The idea of augmenting ligamentous repair as well as reconstruction has recently been proposed by many authors and in different anatomic sites. 10 , 11 , 12 Augmentation may be indicated with variable degrees of chronicity with different techniques, particularly with the use of allografts to protect them until complete healing and ligamentization take place. Early promising results in ACL reconstruction in canine models have been reported.…”
mentioning
confidence: 99%
“…Early promising results in ACL reconstruction in canine models have been reported. 10 , 11 , 12 , 13 However, there is no published technique that describes augmenting an ACL hamstring autograft fixed with a femoral cortical button and Bio-Interference Screw on the tibial side.…”
mentioning
confidence: 99%
“…Similar techniques for preparation of the ACL graft tendon have been described using allograft tissue, 9 , 14 in which a FiberTape is used to secure the construct until the healing process is finished, which usually takes a longer time when using an allograft. However, in such a technique, the FiberTape is suspended over the suture loop of the femoral TightRope, which we think may be a weak point and may be subject to earlier loosening or even failure of the loop of the femoral TightRope because of the higher stresses.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Preliminary results in a canine model showed good results with the use of a quadriceps tendon allograft with suture augmentation (i.e., a quadriceps tendon allograft with an internal brace) without the occurrence of synovitis or premature arthritis. 9 …”
mentioning
confidence: 99%